Efek kandungan serat beras analog terhadap ekspresi GLUT4 otot rangka tikus diabetes - Azka Darajat; Elly Nurus Sakinah; Hairrudin Hairrudin (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2019)
Effect of analog rice’s fiber on skeletal muscles GLUT4 expression in diabetic rats Background: Disruption of glucose transportation in skeletal muscle through GLUT4 becomes a problem in diabetes. Analog rice that had been modified by adding dietary fiber could improve the expression of GLUT4.Objective: This study aims to know the effect of dietary fiber toward GLUT4 expression and to know the dietary fiber percentage in analog rice.Method: The research type is true experimental with post-test only group design. The samples consist of 24 male Wistar rats that are group into 4 groups (n=6 each group). Three groups were induced by giving a high-fat diet for 40 days and streptozotocin (STZ) 35 mg/kg BW was given at 33th day and one group was not induced. After the blood glucose level exceeded 135 mg/dl, the treatment was given. After 3 weeks, the rats were terminated and quadriceps femoris muscle tissue was taken for immunohistochemistry examination using rat GLUT4 polyclonal antibody. GLUT4 expression was quantified using an immunoreactive score (IRS-GLUT4). The data were analyzed using the Kruskal-Wallis test and Spearman test.Results: Statistical analyses showed that there were significant differences between groups with a moderate positive correlation (correlation coefficient=0,651; p=0,003).Conclusion: Dietary fiber in analog rice could improve skeletal muscle GLUT4 expression in Wistar rat diabetic model.